Navigasi Kognitif: Menggali Kemampuan Awal Peserta Didik melalui Lensa Neuroedukasi - A. Hilwa Syauqy Mazidah; Dwi Tantri Indrajita; M. Yunus Abu Bakar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research attempts to reconstruct the understanding of learners’ initial abilities through a neuroeducation approach a multidisciplanary field that blends neuroscience, psycholog, and education. Traditionally, initial abilities are often measured solely through static cognitive pre-test scores. However, through the lens of neuroeducation, initial abilities are viewed as dynamic synaptic networks and cognitive maps already formed in the learners’ brains. This article explores how the concepts of neuroplasticity and cognitive load participate in the assimilation of new information based on existing knowledge. Using a strategy for studying literature, the outcome of the results of the review suggest that proper cognitive navigation, which takes into account the readiness of neural circuits and emotional engagement can prevent learning barriers and accelerate the formation of long-term memory. These findings recommend that educators shift from conventional diagnostic assessments to a more holistic and brain-based mapping of initial abilities to create truly personalized and meaningful learning